The collaborating planner? practitioners in the neoliberal age - Clifford, Ben ca. 20./21. Jh; Tewdwr-Jones, Mark 1968- (The Policy Press, 2013)
Aims to understand how both specific planning and broader public sector reforms have been experienced and understood by chartered town planners working in local authorities across Great Britain